Evaluation of Operational, Organizational, And Public Leadership on The Faculty Board And Department of The Faculty of “Xyz University” - Parimita, Widya; Purwana, Dedi; Nindito, Marsellisa; Hutomo, Moehamad (KnE Social Sciences, 2020)
This research discusses the evaluation of operational, organizational and public leadership by the Faculty Board and Department of the Faculty of XYZ University. The evaluation of effective leadership here refers to the assessment of National Accreditation Agency for Higher Education (NAAHE) in Indonesia. Effective leadership in this sense is leadership that combines three characteristics, namely effectiveness of operational leadership, organizational leadership and public leadership. Descriptive analysis based on data from a questionnaire was employed in this exploratory research. Both academics and non-academics of the Faculty of XYZ University were involved as respondents. The questionnaire was distributed to 69 academics and 27 non-academics. Findings show that the assessment capability of the Dean and Department Coordinator is considered good, and so are their roles and the lecturers’ motivation. Another assessment on the capability of the head of administration division, heads of sub-divisions is also considered good, and so are their roles and the staff’s motivation. Therefore, it is expected that all of the boards are able to maintain and organise activities for both the staff and the lecturers. Keywords: leadership, leadership capability, role of the boards, role of the organization, role of the public